A Novel Bioinspired Multilayered Polymer–Ceramic Composite with Outstanding Crack Resistance. Issue 2 (4th October 2013) - Tushtev, Kamen; Gonsior, Michael; Murck, Michael; Grathwohl, Georg; Rezwan, Kurosch
<x xml:space="preserve">Abstract</x> The feasibility of designing artificial bioinspired ceramic composites with very high crack resistance is demonstrated by bounding of zirconium oxide sheets (70 μm thickness) with only a few micrometers thin adhesive layers. The small amount of organic adhesive (about 5.8 vol%) provides the composite with a crack resistance exceeding 18 MPam1/2, which is about four times as high as that of the basic ceramic material. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>